PEMANFAATAN LIMBAH SERBUK GERGAJI KAYU GALAM (Melaleuca cajuputi Powell) MENJADI BIOETANOL SUMBER ENERGI ALTERNATIF TERBARUKAN - Darmaji Darmaji; Noor Mirad Sari; Yuniarti Yuniarti (Universitas Lambung Mangkurat, 2020)
Along with the increasing population in Indonesia by 1.49% per year according to the central minister of National Population and Family Planning Agency (BKKBN), and depletion of some fuels such as petroleum is expected to experience criticality in less than 10 years, natural gas is 30 years, and coal will spent around 50 years, then alternative energy sources are needed to support the need for energy, one of which is to convert biomass into bioethanolNatural resources in Indonesian are abundant including microorganisms is very possible to make use of biomass into bioethanol, which until now has not been optimally developed. The purpose of this study was to examine the volume biethanol produced from yeast fermentation process and galam wood sawdust and to determine the effect of yeast addition variation and fermentation time on the volume bioethanol produced from galam sawdust waste (Melaleuca cajuputi Powell) .This study uses sawdust gelam sawdust as a substrate with treatment (A) = the amount of yeast addition and (B) = the length of fermentation time. The parameters observed in this study are the volume of bioethanol from variations in the number of yeast additions and the length of fermentation time of sawdust sawdust. The results showed the volume value of ethanol produced from the sawn fermentation process of galam wood (Melaleuca cajuputi Powell) ranged between 3.973 - 7.863 ml. Keywords: Melaleuca cajuputi Powell; Fermentation Time; Volume of Bioetaol